Search for a light charged Higgs boson in the H±→cs channel in proton-proton collisions at √s=13 TeV; Physical Review D; Vol. 102, iss. 7 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2020, 2020)
Title screen